2017
DOI: 10.5185/amlett.2017.1453
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic oxidation of aromatic amines using MnO2@g-C3N4

Abstract: An efficient and direct oxidation of aromatic amines to aromatic azo-compounds has been achieved using a MnO@g- CN catalyst under visible light as a source of energy at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Our results are in agreement with previous reports that showed pristine graphene to be a biocompatible substrate for adherent cells such as fibroblasts and osteoblasts [16,53]. Furthermore, we concur with previous studies that showed graphene surface functionalization with various chemical groups to be a major opportunity to develop various composite materials that can act as the active components in regenerative applications [30,31,34,54]. Interestingly, our work also clearly illustrates that decorating graphene with oxygen groups in various concentrations is easy to accomplish and does not seem to affect the material's interaction with the fibroblast cells used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with previous reports that showed pristine graphene to be a biocompatible substrate for adherent cells such as fibroblasts and osteoblasts [16,53]. Furthermore, we concur with previous studies that showed graphene surface functionalization with various chemical groups to be a major opportunity to develop various composite materials that can act as the active components in regenerative applications [30,31,34,54]. Interestingly, our work also clearly illustrates that decorating graphene with oxygen groups in various concentrations is easy to accomplish and does not seem to affect the material's interaction with the fibroblast cells used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The high peak at 26.73° verifies the stacking reflection of conjugated aromatic systems, showing a graphitic structure with an interlayer distance of 0.326 nm, as shown in Fig. 2(E) 31,32 . The 3D character of graphene oxide is reduced, as indicated by the disappearance of the narrow XRD reflection at 2 θ = 10.8 A°.…”
Section: Resultsmentioning
confidence: 70%
“…2(E). 31,32 The 3D character of graphene oxide is reduced, as indicated by the disappearance of the narrow XRD reflection at 2⊔ = 10.8 A°. Instead, broadband is observed in the case of r-GO, probably due to intralayer spacing, as shown in Fig.…”
Section: Microscopic Characterization Of Nanomaterialsmentioning
confidence: 99%
“…The XRD pattern of pure-g-C 3 N 4 revealed that peaks at 26.73° and 13.37° can be assigned to (002) inter-layer structural packing crystal plane and (100) inter-planar stacking diffraction planes, respectively. The prominent peak at 26.73° confirms the stacking reflection of conjugated aromatic systems, revealing a graphitic structure with an interlayer spacing 0.326 nm [33,38]. The 3D character of graphene oxide is reduced as indicated by the disappearance of the narrow XRD reflection at 2θ = 10.8 Aº.…”
Section: Power and Power Densitymentioning
confidence: 84%
“…Graphitic carbon nitride (g-C 3 N 4 ) nanosheets were synthesized by heating 50 g of urea at 500 °C in air for 3 h [33,34].…”
Section: Preparation Of Graphitic Carbon Nitride Nanosheetsmentioning
confidence: 99%